Vocabulary learning strategies used by first year of EFL students - Rachmawati, Dwita Laksmita (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2017)
This study aims to find out the type of vocabulary learning strategies that the first year students of Faculty of Economics at Merdeka University, Pasuruan commonly use. This study used qualitative research design; that is, to analyze vocabulary learning strategies used by the students. After the students had done to fill the questionnaires, the researcher conducted one-on-one semi-structured interviews to each of the students in order to get depth information about their vocabulary learning strategies. Based on the strategies for discovering meaning; using an English-Indonesia dictionary, guessing meaning from context, and analyzing pictures or gestures were the strong preferences. While, the less-used from discovering meaning were checking for L1 cognate, analyzing affixes and roots, and analyzing part of speech.Â  In terms of strategies for consolidating meaning; studying and practicing meaning within a group, imaging word form, and imaging wordâ€™s meaning were preferred. While, the less-used strategies from consolidating meaning were testing oneself with word tests, skipping or passing new word, and continuing to study word over time.